Tissue Engineering and Regenerative Medicine: Semantic Considerations for an Evolving Paradigm - Katari, Ravi; Peloso, Andrea; Orlando, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2015)
Tissue engineering and regenerative medicine are rapidly evolving fields that are often obscured by a dense cloud of hype and commercialization potential. We find, in the literature and general commentary, that several of the associated terms are casually referenced in varying contexts that ultimately result in the blurring of the distinguishing boundaries which define them. “Tissue engineering” and “regenerative medicine” are often used interchangeably, though some experts vehemently argue that they, in fact, represent different conceptual entities. Nevertheless, contemporary scientists have a general idea of the experiments and milestones that can be classified within either or both categories. Given the groundbreaking achievements reported within the past decade and consequent watershed potential of this field, we feel that it would be useful to properly contextualize these terms semantically and historically. In this concept paper, we explore the various definitions proposed in the literature and emphasize that ambiguous terminology can lead to misplaced apprehension. We assert that the central motifs of both concepts have existed within the surgical sciences long before their appearance as terms in the scientific literature.